Exploring the spatial concentration of foreign employment in Poland under the simplified procedure - Górny, Agata. Autor; Śleszyński, Przemysław. Autor (IGiPZ PAN, 2019)
The unprecedented growth of immigration into Poland after 2013, especially from Ukraine, raises optimism among employers, and concerns among some social and political actors. The goal of this article is to contribute to that discussion, with a view to identifying a detailed geographical localisation of labour migrants employed under the simplified procedure (on the basis of employers’ declarations of a consent to employ a foreigner) – as an important legal channel by which the influx of foreign workers into Poland is taking place. Analyses of the register of declarations for 2012-2017 reveal a certain weakening of the geographical concentration of the foreign labour force in Poland. The highest intensity of foreign employment has been observed in rural areas, while the greatest numbers of declarations for work have been registered in large cities. The geographical distribution of the foreign labour force in Poland has been shaped by activities of employment agencies especially in recent years.
24 cm
Keywords: immigration; Ukrainian migrants; foreign employment; seasonal employment; labour market; simplified procedure